FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN PERBANKAN GO PUBLIC DI BURSA EFEK INDONESIA (BEI) (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2014-2016) - Shasmita Sandra Carissa, 14.05.52.0093; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
The study aims to analyze the factors affecting the timeliness of financial reports on banks listed on the stock exchanges of Indonesia. Factors tested in this study are profitability, leverage, liquidity, firm size and managerial ownership, while timeliness as the dependent variable.The population in this study is all Banking Companies Registered in IDX Period 2014-2016. The sample selection using purposive sampling method and obtained 119 companies.The analysis tool used is the Logistic Regression Analysis at the 5% significance level. As the results, this research found that the hypothesis of a positive effect of firm size on timeliness was received. Hypotheses about the impact of profitability, leverage, liquidity and managerial ownership to timeliness were rejected. Keywords : Timeliness, Profitability, Leverage, Liquidity, Firm Size, Managerial Ownership